Studies of the Effect of Hypnoanasthesia in Reducing Perineal Laceration Suture Pain And Healing of Postpartum Perineal Wounds in Indonesia - Nining Mustika Ningrum; Lusianah Meinawati; Henny Sulistyawati; Mohammed Ismath (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Pervaginal childbirth until now is still the choice of the method of childbirth that is considered the safest and economical. Although the delivery assistance has been done correctly, most women will experience perineal trauma during the vaginal labor process and require perineal suturing. The problem that is often faced by a mother who has a perineal tear is pain during the suturing process and will last until the suture wound is dry and the duration of the healing process of the perineal suture wound. This type of research is quantitative analytics using a Quasi-Experimental research design with the one-group post-test design method. Free variables: Hypnoanasthetic method and bound variables: the pain of perineal suture wounds and healing of perineal wounds. The sample in this study was 66 maternity mothers using purposive sampling techniques. Instruments: Checklists and Observation sheets, data analysis using the Wilcoxon Test. The results showed that after being given the hypnoanastesi method, almost all respondents experienced mild pain during suturing perineal lacerations, namely 87.9% and most respondents took a fast time (2 weeks) in healing perineal wounds, namely 23 respondents (69.7%). This study concludes that the hypnoanastesi method is effective in reducing the pain of suturing perineal lacerations and is effective in the healing process of perineal wounds.